2004
DOI: 10.1021/cm035140x
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Titanium Oxide on Self-Assembled-Monolayer-Coated Gold

Abstract: We demonstrate an atomic layer deposition of TiO2 thin films on self-assembled monolayers of ω-functionalized alkanethiolates. The TiO2 thin films were grown on OH-terminated alkanethiolate monolayer-coated gold by atomic layer deposition at 100 °C. The atomic layer deposition of the TiO2 thin films is self-controlled and extremely linear relative to the number of cycles. Selective deposition of the TiO2 thin film using atomic layer deposition was accomplished with patterned self-assembled monolayers as templa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
89
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 22 publications
1
89
0
Order By: Relevance
“…A large fraction of this work does not involve growth on the organic but instead the use of a SAM to block the growth of an inorganic thin film. 75 In a mixed layer of these same SAMs, it was found that the morphology of the subsequently deposited TiO 2 depended on the relative surface concentration of uOH versus uCH 3 terminations. Concerning growth on SAMs, the ALD of WC x N y , using B͑C 2 H 5 ͒ 3 , WF 6 , and NH 3 as the thin film precursors, has been examined on SAMs possessing uBr, uCH 3 , and uCN terminations.…”
Section: Introductionmentioning
confidence: 98%
“…A large fraction of this work does not involve growth on the organic but instead the use of a SAM to block the growth of an inorganic thin film. 75 In a mixed layer of these same SAMs, it was found that the morphology of the subsequently deposited TiO 2 depended on the relative surface concentration of uOH versus uCH 3 terminations. Concerning growth on SAMs, the ALD of WC x N y , using B͑C 2 H 5 ͒ 3 , WF 6 , and NH 3 as the thin film precursors, has been examined on SAMs possessing uBr, uCH 3 , and uCN terminations.…”
Section: Introductionmentioning
confidence: 98%
“…Titanium dioxide (TiO 2 ) has many useful electrical and optical properties, such as a high refractive index, high dielectrical permittivity, semiconductivity, excellent transmittance of visible light, and so forth, which make TiO 2 films useful in many fields, like microelectonics [2], optical cells [3], solar energy conversion [4], efficient catalyst [5]. Accordingly, fabrication of thin films and micropatterns of TiO 2 has been attempted by various methods in the past decades [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This feature has permitted the ability to pattern polymer thin films on the nanometer scale. (3) Microcontact printing (µCP) [11][12][13][14][15]. During this process, the PDMS stamp was used to transfer a kind of self-assembled monolayers (SAMs) patterns to the substrate, and then the patterned SAMs could be used as the templates for the deposition or etching materials.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a single surface can be modified to have regions of two or more different properties depending on the choice of SAM. Seo et al demonstrated a change of the properties of a Au surface by using two different SAMs, octadecanethiol (ODT) and mercaptoundecanol (MOU) [37]. These two SAM molecules have same thiol head group but different tail groups: CH 3 termination and OH termination for ODTand MOU, respectively.…”
mentioning
confidence: 99%